Characterization of the χψ subcomplex of Pseudomonas aeruginosa DNA polymerase III - El Houry Mignan, Sirine (BioMed Central, 2011)
BACKGROUND: DNA polymerase III, the main enzyme responsible for bacterial DNA replication, is composed of three sub-assemblies: the polymerase core, the β-sliding clamp, and the clamp loader. During replication, single-stranded DNA-binding protein (SSB) coats and protects single-stranded DNA (ssDNA) and also interacts with the χψ heterodimer, a sub-complex of the clamp loader. Whereas the χ subunits of Escherichia coli and Pseudomonas aeruginosa are about 40% homologous, P. aeruginosa ψ is twice as large as its E. coli counterpart, and contains additional sequences. It was shown that P. aeruginosa χψ together with SSB increases the activity of its cognate clamp loader 25-fold at low salt. The E. coli clamp loader, however, is insensitive to the addition of its cognate χψ under similar conditions. In order to find out distinguishing properties within P. aeruginosa χψ which account for this higher stimulatory effect, we characterized P. aeruginosa χψ by a detailed structural and functional comparison with its E. coli counterpart. RESULTS: Using small-angle X-ray scattering, analytical ultracentrifugation, and homology-based modeling, we found the N-terminus of P. aeruginosa ψ to be unstructured. Under high salt conditions, the affinity of the χψ complexes from both organisms to their cognate SSB was similar. Under low salt conditions, P. aeruginosa χψ, contrary to E. coli χψ, binds to ssDNA via the N-terminus of ψ. Whereas it is also able to bind to double-stranded DNA, the affinity is somewhat reduced. CONCLUSIONS: The binding to DNA, otherwise never reported for any other ψ protein, enhances the affinity of P. aeruginosa χψ towards the SSB/ssDNA complex and very likely contributes to the higher stimulatory effect of P. aeruginosa χψ on the clamp loader. We also observed DNA-binding activity for P. putida χψ, making this activity most probably a characteristic of the ψ proteins from the Pseudomonadaceae.